2015
DOI: 10.1002/jcb.25241
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3β Stimulates BMP Signaling and Decreases SOST Expression Which Results in Enhanced Osteoblast Differentiation

Abstract: Both bone morphogenetic protein (BMP) and Wnt signaling have significant roles in osteoblast differentiation and the interaction between BMP and Wnt signaling is well known. Sclerostin is an important inhibitor of bone formation, inhibiting Wnt signaling and downstream effects of BMP such as alkaline phosphatase activity and matrix mineralization in vitro. However, little is known about the effect of BMP and Wnt signaling interaction on the regulation of SOST, the gene encoding sclerostin. Possibly, uncoupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…We found that CXCL13 was higher in treatment group than in the other two groups. ALP, the alkaline phosphatase, was regarded as the early marker of osteoblast phenotype and differentiation [37,38]. In this study, the increase rate of ALP was significantly lower in diabetic group than in the other two groups at various time points, suggesting a worse osteoblast differentiation in the diabetic group.…”
Section: Discussionmentioning
confidence: 51%
“…We found that CXCL13 was higher in treatment group than in the other two groups. ALP, the alkaline phosphatase, was regarded as the early marker of osteoblast phenotype and differentiation [37,38]. In this study, the increase rate of ALP was significantly lower in diabetic group than in the other two groups at various time points, suggesting a worse osteoblast differentiation in the diabetic group.…”
Section: Discussionmentioning
confidence: 51%
“…BMP-2-induced up-regulation of SOST has also been shown by a number of studies [Sutherland et al, 2004, Yu et al, 2011bSchoeman et al, 2015]. Although SOST is considered to be an antagonist of canonical Wnt-signaling in the first line, Sutherland et al [2004] and others [Schoeman et al, 2015] could show that BMP-4 as well as BMP-2 induced SOST expression.…”
Section: Discussionmentioning
confidence: 69%
“…Although SOST is considered to be an antagonist of canonical Wnt-signaling in the first line, Sutherland et al [2004] and others [Schoeman et al, 2015] could show that BMP-4 as well as BMP-2 induced SOST expression. The negative effects of BMP-4-induced SOST could be inhibited by addition of low doses of glycogen synthase kinase (GSK) 3b inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP‐2 is even used in clinical practice for accelerated healing of fractures and for spinal fusions 30, 34. In our recent study using the murine cell‐line KS483, a combination of BMP‐4 and GIN (a stimulator of Wnt‐signalling) was found to enhance mineralization and decrease the expression of Sclerostin (an inhibitor of bone formation) compared to BMP‐4 alone 35. Therefore, we also stimulated cells with OM supplemented with either GIN or a combination of GIN and BMP‐2 or BMP‐6.…”
Section: Discussionmentioning
confidence: 99%